2013
DOI: 10.3928/1081597x-20130823-01
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Subjective Classifications of Corneal Topography Maps From LASIK Candidates

Abstract: There was significant inter-observer variability in the subjective classifications using the same scale, and significant intra-observer variability between scales. Changing from an absolute to a normative scale increased the scores on the classifications by the same examiner, but significant inter-observer variability in the subjective interpretation of the maps still persisted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…Subjective classification was performed by an independent fellowship trained refractive surgeon who did not know the outcome of LASIK in a similar method as described by Ramos and coworkers (16) . The RSB was calculated considering the preoperative thinnest value from Pentacam measurements, maximal ablation depth and estimated flap thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective classification was performed by an independent fellowship trained refractive surgeon who did not know the outcome of LASIK in a similar method as described by Ramos and coworkers (16) . The RSB was calculated considering the preoperative thinnest value from Pentacam measurements, maximal ablation depth and estimated flap thickness.…”
Section: Methodsmentioning
confidence: 99%
“…The ERSS was validated by a second study (14) , which confirmed abnormal corneal topography and age as the most important variables for predicting ectasia risk Even though the ERSS represented an advance on the ability to detect ectasia risk (15) , there were still 8% of false negatives, and 6% of false positives in the original studies. The subjective nature of the classifications of corneal topography limits the repeatability of the approach (16) , which may help explain up to 25% of false negatives in an independent retrospective study of ectasia cases (17) . In addition, over 50% of false positives may occur if a young population of stable LASIK patients is evaluated.…”
Section: Avaliação De Suscetibilidade Para Ectasia Antes De Lasik: O mentioning
confidence: 99%
“…Considering that there is high variability on subjective classifications of color coded maps, 17 objective, and validated criteria is essential for diagnostic interpretation, and for the clinician to take full advantage of the diagnostic technologies. 8,18,20,27 The analysis, using advanced corneal characterization of the preoperative state of cases that developed ectasia and of the ones that are stable after LVC represents the closest to ideal populations for the development and testing sensitivity and specificity of ectasia risk assessment approaches.…”
Section: Conclusion and Future Remarksmentioning
confidence: 99%
“…In fact, Ramos et al reported significant interobserver variability in subjective classifications of corneal topography maps. 17 Changing from an absolute to a normative scale increased the scores on the classifications by the same examiner, with significant intraobserver variability. 17 Objective quantitative indices, such as the classic Rabinowitz inferior-superior dioptric asymmetry value (I-S) and the keratoconus percentage index (KISA), and qualitative pattern of asymmetric bow tie with skewed radial axes was an attempt to add objective measurement to the previous subjective evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation